A case of Kikuchi-Fujimoto disease misdiagnosed as Hodgkin's lymphoma: the importance of second opinion - (:unkn) unknown (ZERBINIS MEDICAL PUBL, 2009)
Kikuchi-Fujimoto disease (KFD), a rare clinicopathological entity, is a benign and self-limiting disease. It was first described in 1972 by Kikuchi and Fujimoto in Japan independently KFD is prevalent in Asia, although it may be seen in wide geographical areas, including Turkey. It mainly affects young women. Cervical lymphadenopathy is the most prominent sign and should be differentiated from lymphoproliferative, autoimmune, and infectious diseases. We report on a 30-year-old female patient who was referred to our medical oncology unit for chemotherapy and/or radiotherapy with diagnosis of Hodgkin's lymphoma. Ultimately her diagnosis was corrected as KFD after second opinion of the pathology, specimens. We herein provide a brief review about KFD and the importance of second opinion of the pathology specimens.
Keywords: Hodgkin's lymphoma; Kikuchi Fujimoto disease; misdiagnosis; lymphadenopathy; lymphoma; second opinion; SURGICAL PATHOLOGY